2015
DOI: 10.1002/adma.201503648
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D Metal–Organic Framework Nanosheets

Abstract: A facile surfactant-assisted bottom-up synthetic method to prepare a series of freestanding ultrathin 2D M-TCPP (M = Zn, Cu, Cd or Co, TCPP = tetrakis(4-carboxyphenyl)porphyrin) nanosheets with a thickness of sub-10 nm is developed. As a proof-of-concept application, some of them are successfully used as new platforms for DNA detection. The Cu-TCPP nanosheet-based sensor shows excellent fluorescent sensing performance and is used for the simultaneous detection of multiple DNA targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
839
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,026 publications
(895 citation statements)
references
References 51 publications
31
839
2
5
Order By: Relevance
“…Previous high-throughput array analyses have demonstrated that the expression of miRNAs present substantial variances in tumors [18,19]. Overexpression of miRNAs may contribute to its oncogenesis by downregulating tumor suppressors, whereas underexpression of miRNAs may negatively regulate oncogenes or factors related to tumorigenesis and progression [20]. Thus, we explore comprehensive miRNAs profile in NSCLC with LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous high-throughput array analyses have demonstrated that the expression of miRNAs present substantial variances in tumors [18,19]. Overexpression of miRNAs may contribute to its oncogenesis by downregulating tumor suppressors, whereas underexpression of miRNAs may negatively regulate oncogenes or factors related to tumorigenesis and progression [20]. Thus, we explore comprehensive miRNAs profile in NSCLC with LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Most current synthesis has focused on three routes: 33 assembly at an interface, 30,34 synthesis of nanosheets in bulk solution, 31,32 and liquid-phase exfoliation of weakly bound 2D layered materials (including with the assistance of surfactants). 35,36 To the best of our knowledge, there have been no reports of the synthesis of nanosheets from 3D framework materials, as this requires the breaking of strong metal–ligand bonds. This work, by showing the feasibility of chemically selective cleavage of these strong bonds, suggests that harnessing the huge variety of 3D MOFs as precursors for metal–organic nanosheets is a promising strategy for the synthesis of new low-dimensional materials.…”
Section: Introductionmentioning
confidence: 99%
“…The recently reported strategies like calcinations at high temperature may sacrifice MOFs' intrinsic molecular metal active sites8, while hybridization with secondary conductive supports (polyaniline9, graphene10 and so on) may block their intrinsic micropores, and the bulk conductive MOF has limited meso- and macro-porosity (tens of nanometres to several micrometres) for effective mass transport during electrocatalysis7. Very recently, a few two-dimensional (2D) MOFs have been synthesized1112131415, but the majority of 2D MOFs reported to date have been prepared in powder form, and little effort has been devoted to increasing the macro-/meso-porosity, conductivity or number of catalytic centres.…”
mentioning
confidence: 99%